Students' Ability In Understanding Reading Passage Questions At The Eighth Grade Of SMP Muhammadiyah 5 SurakartaIn 2013/2014 Academic Year - Syamsiah., Nurul; , Aryati Prasetyarini, S.Pd, M.Pd; , Dr. Dwi Haryanti, M.Hum (2014)
The objectives of this research are to describe (1) the students' ability in understanding reading passage questions at the eighth grade of SMP Muhammadiyah 5 Surakarta in 2013/2014 academic year, (2) the most difficult question in understanding reading passage questions, and (3) the students' strategies in understanding reading passage questions. This research belongs to descriptive research. The data of this research are the students' test result, verbatim of interview, and field notes of observation, which are collected through observation, interview, and test. The data are analyzed in two ways, quantitatively and qualitatively, by using a simple descriptive statistic analysis and using Miles & Huberman's interactive model of data analysis technique which consists of data collection, data reduction, data display, and drawing conclusion or verification. The data credibility of this research is checked by using triangulation of source and triangulation of technique. The result of this research showed that (1) the students' ability in understanding reading passage questions at the eighth grade of SMP Muhammadiyah 5 Surakarta in 2013/2014 academic year is in a Fair level, because the percentage indicates in 62.29%; (2) the most difficult question in understanding reading passage questions according to the eighth grade of SMP Muhammadiyah 5 Surakarta in 2013/2014 academic year is the Indirectly Answered Questions; (3) in understanding reading passage questions at the eighth grade of SMP Muhammadiyah 5 Surakarta in 2013/2014 academic year, the students did not use a certain strategy because they did not know the kinds of strategy in answering the reading passage questions.